2021
DOI: 10.3390/su13094624
|View full text |Cite
|
Sign up to set email alerts
|

Geosites and Geotourism in the Local Development of Communities of the Andes Mountains. A Case Study

Abstract: The inventory and assessment of a geosite in a territory provides a sound basis for the protection and use of its geological heritage. This article aims to evaluate the most relevant geosites in the province of Chimborazo (Ecuador), applying the Spanish Inventory of Sites of Geological Interest (IELIG, in Spanish) method, and proposing alternatives for geotourism development in the studied area. The methodological process was based on: (i) the inventory and preliminary selection of geosites; (ii) a semi-quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 70 publications
1
14
0
2
Order By: Relevance
“…Although the Ecuadorian government has recently proposed a tourist route, known as the Spondylus route (Ministerio de Transporte y Obras Públicas 2013 ), in the province, our aim was to create strategic itineraries with significant scientific, educational, and tourism values seeking the development of local communities. Similar initiatives have been published in other provinces of the country by the CIPAT-ESPOL research group (Carrión-Mero et al 2021b , a ).…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 67%
“…Although the Ecuadorian government has recently proposed a tourist route, known as the Spondylus route (Ministerio de Transporte y Obras Públicas 2013 ), in the province, our aim was to create strategic itineraries with significant scientific, educational, and tourism values seeking the development of local communities. Similar initiatives have been published in other provinces of the country by the CIPAT-ESPOL research group (Carrión-Mero et al 2021b , a ).…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 67%
“…Within the country, some of the few evaluations of geosites with glacial origin are those carried out in the Chimborazo Province [95] and Ruta Escondida (Quito) [96,97]. These studies presented significant values for promotion and sustainable management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is worth mentioning that mobile applications are tools that after their implementation usually require little financial input, apart from the costs of maintenance and further development [55]. Very few similar studies were found in the international literature, although many studies have been found to deal with smart tourism and smart tourism tools [8,19,21,23,25,29,34,47,48] and there is a fact that such studies are lacking in Ecuador. For this reason, it is recommended to find innovative ways of increasing the frequency of collecting relevant tourist data so that the local tourist industry can be more connected to the requirements of the tourists, making it able to update its offerings on smart and sustainable tourist products, an approach that could be helpful since a successful implementation of smart tourism destinations has the potential of attracting foreign direct investment, thus ensuring sustainable development [56].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, about 35% of Ecuadorians purchase products or services over the Internet, tourism services being one of the categories with the highest consumption [18]. The province of Chimborazo hosts many tourist attractions belonging to the natural and sociocultural categories and attracts a considerable number of national and international tourists year after year [19]. Within the province, the Riobamba Canton is known to hold tourist attractions with a lot of potential and the Development Plan of Riobamba "20-30" indicates that the cantonal government seeks to use the latest technologies to enhance the attendance to these attractions in the next 10 years [20].…”
Section: Introductionmentioning
confidence: 99%